Disability Narratives in Sports Communication: Tokyo 2020 Paralympic Games’ Best Practices and Implications - Kolotouchkina, Olga (2021)
The Paralympic Games have become a relevant social and communication tool for the enhancement of global awareness and understanding of disability. The increasing visibility of this kind of global sports event, as well as the efforts of public authorities to make their host cities more accessible, evidence a relevant shift to new urban barrier-free experiences and discourses concerning disability. This research is guided by an exploratory case study approach to assess the disability representation and narratives within the context of the 2020 Tokyo Paralympic Games. The examination of some innovative communication strategies fostering the visibility of disability reveals a series of effective practices implemented in Japan. The focus on the personification of para-athletes, the celebration of public events to experience first-hand para-sports disciplines, as well as the engagement of school-children and young people in para-sports initiatives are predominant in the communication efforts of Tokyo 2020 in the pre-games period.